Remarks on alternative solutions to punishment in petty offences law - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Given the need for the state to respond to low-level acts such as petty offences, there is still a noticeable search for an optimal model of punishment for these acts. It is known that penal means of punishment do not always fulfil their purpose. Therefore, the petty offences law, which is closer to the principle of opportunism, apart from the inconvenience of penal solutions towards the perpetrator of the offence, assumes the possibility of applying non-penal measures in the form of educational influence measures. The article presents the essence of the measures included in Article 41 of the Code of Petty Offences and draws attention to the legislative imperfections in this respect and many interpellation- related doubts. The analysis of educational measures indicates that they could play an important role in changing the hierarchy of the model of punishment for offences. However, it is necessary for the legislator to consider changes, including those indicated in this study, in order to prioritize this form of punishment for minor prohibited acts in the form of petty offences.
Keywords: offence; punishment; educational purpose; educational influence means; alternative to punishment